Measurement of the ratios of the Z / γ* + ≥ n jet production cross sections to the total inclusive Z / γ* cross section in p over(p, -) collisions at sqrt(s) = 1.96 TeV - Abazov, V; Abbott, B; Abolins, M; Acharya, B; Adams, M; Adams, T; Agelou, M; Ahn, S; Ahsan, M; Alexeev, G; Alkhazov, G; Alton, A; et al. (2008)
We present a study of events with Z bosons and associated jets produced at the Fermilab Tevatron collider in p over(p, ̄) collisions at a center of mass energy of 1.96 TeV. The data sample consists of nearly 14 000 Z / γ* → e+ e- candidates corresponding to an integrated luminosity of 0.4 fb-1 collected with the DØ detector. Ratios of the Z / γ* + ≥ n jet cross sections to the total inclusive Z / γ* cross section have been measured for n = 1 - 4 jets, and found to be in good agreement with a next-to-leading order QCD calculation and with a tree-level QCD prediction with parton shower simulation and hadronization.